2018
DOI: 10.1177/0300060518801457
|View full text |Cite
|
Sign up to set email alerts
|

Butorphanol effectively prevents etomidate-induced myoclonus: a pooled analysis of 788 patients

Abstract: Objective To evaluate the efficacy of pre-injection of butorphanol on etomidate-induced myoclonus during anesthesia induction. Methods Randomized controlled trials (RCTs) of the ability of butorphanol to prevent etomidate-induced myoclonus were collected by searching PubMed, Cochrane Library, CNKI, and WanFang databases, from the day of database establishment until May 2017. The literature was screened independently by two evaluators, and the data were then extracted and independently evaluated. Finally, meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(28 citation statements)
references
References 10 publications
(16 reference statements)
0
28
0
Order By: Relevance
“…Other studies reported that several drugs could effectively prevent the occurrence of the myoclonus induced by etomidate, such as dezocine, lidocaine and midazolam, fentanyl and remifentanil. [15][16] This study has two limitations: we could not track long-term mortality or survival rate and did not compare the effects of propofol or etomidate in non-burn patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported that several drugs could effectively prevent the occurrence of the myoclonus induced by etomidate, such as dezocine, lidocaine and midazolam, fentanyl and remifentanil. [15][16] This study has two limitations: we could not track long-term mortality or survival rate and did not compare the effects of propofol or etomidate in non-burn patients.…”
Section: Discussionmentioning
confidence: 99%
“…Criteria 1, 2, 4, 5, and 10 relating to the review question, inclusion criteria, study appraisal, and recommendations for quality and practice were met by all included systematic reviews. Four of 8 systematic reviews stated the likelihood of publication bias 4,8,9,18 ; however, only 1 review 18 specifically mentioned a search of gray literature, so it is possible that up to 87.5% of reviews had some form of this bias (criterion 9). No reviews were excluded based on methodological quality.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Quantitative findings were also extracted and are provided in the following section. Upon close inspection, 12 primary studies cited in 8 reviews [4][5][6]8,9,[16][17][18] were found to be duplicated across some reviews, resulting in a total of 48 unique RCTs. As the aim of an umbrella review is not to pool data from included reviews, individual data that were duplicated across reviews were not separated out in the final analysis for an overall estimate of effect.…”
Section: Characteristics Of Included Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variety of drugs available is appreciated by many anesthesiologists. Some traditional pairwise meta-analyses have evaluated the efficacy of two drugs or a drug versus a placebo to guide agent selection ( 8 15 ). However, when faced with a wide range of interventions, most anesthesiologists still struggle to choose the best option, and instead, use the drug empirically.…”
Section: Introductionmentioning
confidence: 99%